The Relationship Between Contact History, Clean And Healthy Living Behavior, Smoking Behavior And Pulmonary Tuberculosis In Youth At The Outpatient Pulmonary Polyclinic In Regional General Hospital In Kendari: Pulmonary Tuberculosis In Youth - Devi Effendy; Wa Ode Saktilawati; Siti Nufadilah H; Hariati Lestari; Febriana Muchtar (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis transmitted through human droplets which have been infected with the bacterium. There are many risk factors led to an increased the incidence of TB. The risk factors that had a role on the incidence of TB were internal factors and external factors. The purpose of this study was to determine the risk factors for the incidence of pulmonary tuberculosis in adolescents at the outpatient pulmonary clinic at Regional General Hospital of Kendari in 2022. Methods: This type of research was a quantitative with an analytic observational using a case-control approach. The sampling technique in this study was purposive, with a sample size of 70 people consisting of 35 case samples and 35 control samples. Results: This study found a significant effect of contact history on the incidence of pulmonary TB in the youth group (p <0.05; OR=2.300; 95% CI = 0.130-40.545). There is a significant effect of PHBS on the incidence of pulmonary tuberculosis in the youth group (p <0.05; OR=1.364; 95% CI = 1.005-1.850). Smoking behavior has a significant effect on the incidence of pulmonary TB in adolescents (p <0.05; OR = 10.083; 95% CI = 1.112-91.417). Conclusions: This study concluded that the variable of contact history, PHBS, and smoking behavior influence the incidence of pulmonary TB to the youth group  at the outpatient pulmonary polyclinic in regional general hospital  of Kendari in 2022.